Pengaruh Komptensi Sumber Daya Manusia (SDM) terhadap Kualitas Laporan Keuangan Desa - Hermansyah Hermansyah; Syahrul Sidik; Sahban Aripin; Reyhan Jomono Alfikhry; Jaka Adi Pratama; Sawal Fitriadi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the influence of human resource (HR) competence on the quality of village financial statements. Human resource competence is an important factor in realizing transparent and accountable village financial governance, especially in the preparation of financial statements as a form of accountability of the village government to the community and other stakeholders. The research method used is a quantitative method with a survey approach. The number of samples in this study was 104 respondents consisting of village officials in Lalan District, Musi Banyuasin Regency. The data collection technique was carried out through the distribution of questionnaires prepared based on indicators of human resource competence and the quality of village financial statements, then analyzed using linear regression analysis. The results of the study show that the competence of human resources (HR) has a positive and significant effect on the quality of village financial statements. This finding indicates that the better the level of knowledge, skills, and abilities of village officials, the higher the quality of the financial reports produced. Therefore, improving human resource competencies through training, mentoring, and strengthening the village financial management system is a strategic step in supporting the creation of effective, transparent, and sustainable village financial management.